Optical lattice quantum Hall effect - Palmer, R; Klein, A; Jaksch, D (2008)
We explore the behavior of interacting bosonic atoms in an optical lattice subject to a large artificial magnetic field. We extend earlier investigations of this system where the number of magnetic flux quanta per unit cell α is close to a simple rational number. Interesting topological states such as the Laughlin and Read-Rezayi states can occur even if the atoms experience a weak trapping potential in one direction. An explicit numerical calculation near α=1/2 shows that the system exhibits a striped vortex lattice phase of one species, which is analogous to the behavior of a two-species system for small α. We also investigate methods to probe the encountered states. These include spatial correlation functions and the measurement of noise correlations in time-of-flight expanded atomic clouds. Characteristic differences arise which allow for an identification of the respective quantum Hall states. We furthermore discuss that a counterintuitive flow of the Hall current occurs for certain values of α. © 2008 The American Physical Society.